Effects of multisession prefrontal cortex tDCS or taVNS on stress, perceived stress and sleep quality: a double-blind, randomized controlled study - dos Reis, Laya Dalila; Pereira Generoso, Laura; Pereira, Gabrielly Santos; Teixeira Barú, João Paulo da Silva; Candido, Natalie Lange; Maziero Capello, Maria Gabriela; de Castro, Renato Ortolani Marcondes; Cardoso, Edvaldo José Rodrigues; Scoz, Robson Dias; Ferreira, Luciano Maia Alves; da Silva, Marcelo Lourenço; da Silva, Josie Resende Torres (Frontiers in Psychology, 2024)
Chronic stress is a condition characterized by prolonged stimulation, leading to mental and physical weakness. It can have detrimental effects on individuals' mental health and cognitive function, potentially causing various health issues.This article explores the potential of non-invasive neuromodulation techniques, specifically transcranial direct current stimulation (tDCS) and transcutaneous auricular vagus nerve stimulation (taVNS), in managing chronic stress and improving sleep quality. The study conducted a randomized, double-blinded, controlled trial with participants experiencing chronic stress. In total, 100 participants were randomly assigned to one of four conditions: the anodal tDCS group (n = 50), the sham tDCS group (n = 50), the taVNS group (n = 50), or the sham taVNS group (n = 50). Within each condition, participants received 5 sessions of either active treatment or sham treatment, with 20 minutes of tDCS over the DLPFC (2 mA) for the tDCS groups, or taVNS on the left ear (20Hz) for the taVNS groups. At baseline, post-intervention, and four weeks thereafter, we evaluated stress using the Lipp's Inventory of Stress Symptoms for Adults (LSSI), perceived stress through the Perceived Stress Scale (PSS-10), and sleep quality via the Pittsburgh Sleep Quality Index (PSQI). The tDCS and taVNS interventions resulted in reduced stress levels, improved sleep quality, and enhanced perception of stress. These findings suggest that tDCS and taVNS hold promise as effective treatments for chronic stress, offering a safe and accessible approach to improving individuals' well-being and overall quality of life.